The role of the Chief Information Officer (CIO) in Hospital Management Structure - Książek, Piotr (Polish Journal of Public Health, 2010)
The main objective of the article is to describe the role of the CIO in the current management structure of hospital. Due to the growing role of information, authors discuss approach to functions of CIO and future expectations.